EVALUASI PELAKSANAAN PENERIMAAN PASIEN LAMA RAWAT JALAN DI RSUD WATES - , MEI DITA NURCAHYANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Outpatient Registration Section is the first place visited by the patient or the patient's family before they get health care. The Patient Registration on the service process is first started. Outpatient admissions process is included into the organization of medical records. In this study, the authors focus on the implementation of patient acceptance of outpatient long. Old patient registration process requires outpatient longer time if dibandingakan with existing standards. By default, the time required to enroll patients in five minutes but implementation takes seven minutes longer. It allows the patient did complain and the effect on customer satisfaction. In this study the authors will see how the implementation of the outpatient registration time and know the obstacles that occur in patients receiving long activities in the hospital outpatient Wates. Objective: To determine the execution time of patients receiving outpatient care in hospitals Wates and know the obstacles in the implementation of patient acceptance of outpatient long. Method: The type of research used in this study was a descriptive study with a qualitative approach. The research design used in this study is a cross sectional. The subjects were three admissions while researchers used triangulation Kapala part on interviews with medical support services. Collecting data using interviews, observations, and documentation. Results: Implementation of patient acceptance of its existing SOP but there has been no use of the registration queue number as indicated on the SOP. There is no SOP for patients receiving Jamkseda, Jamkesda non Cards, Jamkesos, Jampersal, and Social Security. There are several obstacles that occur from factors such as man (human), machine (tool), method (how), and environment (environment). Such as the length of making bail, delay in medical record file in the clinic until the destination, file duplication, less rigorous officers when interviewing the patient, as well as away polyclinic which inhibit the distribution of files. Those things that hinder service and peeps complain of patient care and lead to dissatisfaction.